HUMAN BEING’S ARCHITECTURES: The healthy and sacred domestic space - Aresta, Marco (2021)
This article aims to expose the importance of architectural space and its influence on behaviors and states of mind of human beings. When we talk about healthy architec-ture, we talk about shapes and spaces that make us feel better, that make us better peo-ple. Knowing the biology and psychology of the human being we can determine comfort environments supported by the design of spaces and furniture. The experience of the last 10 years, in single-family housing projects in which the discoveries of neuro-science have been used, supported by biomimicry and the ancestry of geometry, led us to concrete results that show that the spaces of domestic architecture in which certain geometries are used can be decisive in guaranteeing the health of each occupant and each family.